Single-cell profiling of T cells uncovers a tissue-resident memory-like T-cell subset associated with bidirectional prognosis for B-cell acute lymphoblastic leukemia - Lai, Wenpu; Wang, Xiaofang; Liu, Lian; Xu, Ling; Mao, Lipeng; Tan, Jiaxiong; Zha, Xianfeng; Zhan, Huien; Lei, Wen; Lan, Yu; Chen, Guobing; Li, Yangqiu; et al. (Frontiers in Immunology, 2022)
Introduction The character and composition of leukemia-related T cells are closely related to the treatment response and prognosis for patients. Though B cell-acute lymphoblastic leukemia (B-ALL) patients have benefited from immune-based approaches, such as chimeric antigen receptor T cells therapy, some of them still end with poor prognosis, especially for adult patients. Therefore, deep understanding of the developmental relationship between T cell subtypes in relation to B-ALL patient prognosis is urgently needed. Methods We analyzed the peripheral blood T cell single-cell RNA sequencing data of three B-ALL patients, using data from 11 healthy individuals as controls. In total, 16,143 and 53,701 T cells from B-ALL patients and healthy adults, respectively, were objectively analyzed for detailed delineation of 13 distinct T cell clusters. Cluster-specific genes were used as marker genes to annotate each T cell subtype. Results Unbiased analysis enabled the discovery of circulating CD103+ T cell (CD3+CD103+MKI67+), also defined as tissue-resident memory-like T (Trm-like) cell, populations were elevated in B-ALL patients, which expressed high level of cell proliferation and exhaustion related genes. In addition, cell fate trajectory analysis showed these Trm-like cells, which shared T-cell receptor (TCR) clonotypes with exhausted T (Tex) cells and effector T (Teff) cells, were supposed to transition into Teff cells; however, mainly transformed into Tex cells in leukemia environment. More importantly, Trm-like cells transformation into Teff cells and Tex cells potentially led to favorable or poor prognosis for B-ALL patients, respectively. Conclusion In sum, a circulating Trm-like cell subset with high level expression of cell proliferation and exhaustion related genes was elevated in B-ALL patients. The bidirectional developmental potential of these T cells into Teff or Tex is closely associated with favorable or poor prognosis, respectively. Together, our study provided a unique insight of alteration of leukemia related T cells, also showed a potential immunotherapy direction and prognosis assessment model for B-ALL patients.